Factors Affecting Service Performance of Hotel Employees in Chonburi Province - Chanphet, Panadda; Pinyosiripan, Siriwan; Sadangharn, Pornrat (Rajapark Journal, 2024)
The aim of this study is fourfold: 1) To explore the relationship between emotional intelligence and the service performance of frontline employees in the hotel business in Chonburi. 2) To examine the relationship between emotional intelligence and work engagement. 3) To investigate the relationship between work engagement and service performance, and 4) to analyze the mediating role of work engagement on the relationship between emotional intelligence and service performance. Purposive sampling was designed with 300 employees working full-time in a hotel located in Chonburi. Data was collected via questionnaire and descriptive statistics, including frequency, percentage, average, and standard deviation, and hypotheses were tested by analyzing structural equation models employed to analyze data. The results indicated that 1. service performance was influenced by emotional intelligence; 2. emotional intelligence is also associated with employee work engagement; 3. work engagement has a positive relationship with service performance; and 4. the relationship between emotional intelligence and service performance was mediated by work engagement.